Federal Cocaine Sentences Before and After Passage of the Fair Sentencing Act of 2010 - Wells, Makeela J. (American journal of criminal justice, 2022)
Passage of the Fair Sentencing Act (FSA) in 2010 reduced the 100-to-1 powder-crack cocaine quantity ratio to 18-to-1 to lessen the disparity between powder and crack cocaine sentences. Prior to FSA, individuals sentenced for 5 g of crack cocaine received similar sentences to those sentenced for 500 g of powder cocaine. The current study examined federal cocaine sentences both before and after the FSA. Specifically, it explored if the FSA has an impact on the influence of race/ethnicity and drug-related variables on the decision to incarcerate, incarceration length, and receiving a downward departure. Using data from the United States Sentencing Commission (USSC) for the years 2005-2009 (pre-FSA) and 2011-2015 (post-FSA), results showed an overall decrease in the number of federal cocaine cases and average incarceration length after passage of the FSA. These findings revealed that FSA is continuing the efforts to reduce the sentencing disparity between federal crack and powder cocaine offenses. However, results seemed to suggest that the policy may exacerbate racial and ethnic disparity in federal cocaine cases through use of downward departures.